Predicting decisions to purchase from sponsors of the Vancouver 2010 Olympics. (2014) - Potwarka, Luke R.; McCarville, Ron E.; Kaplanidou, Kyriaki
Our purpose was to understand motivational factors associated with peoples' decision to purchase products/services from sponsors of the Vancouver 2010 Olympics. To achieve this purpose, we employed and extended Ajzen's theory of planned behaviour (TPB). A three-phase, mixed method data collection process was completed among a sample of young adults living in Canada (N = 471). Our extended TPB model accounted for 61% of the variance in intention and 58% of the variance in self-reported purchase behaviour. Attitude toward the behaviour, subjective norms, descriptive norms and past behaviour emerged as significant predictors of purchase intention. Intention, in turn, predicted self-reported purchase behaviour. We conclude that the TPB can offer sponsorship researchers a sound theoretical model for understanding purchase decisions. Implications for sponsorship marketers are discussed.